Complex symmetric weighted composition operators on the Fock space in several variables - Hai, Pham Viet (2019)
We characterize all selfadjoint as well as all unitary anti-linear weighted composition operators acting on the Fock space . Then we obtain a complete description of anti-linear weighted composition operators that are conjugations. These results allow us to determine which bounded linear weighted composition operators can be complex symmetric on the Fock space .